Technical Study Of Anchovy Catch Effort With Purse Seine At Larangan Coastal Fishing Port, Tegal Regency - Kusnandar Kusnandar; Sri Mulyani; Agung Ferdinand Wera; Dian Sutono Hs (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Larangan Coastal Fishing Port, located in Tegal Regency, Central Java, is one of the ports in Central Java with a fairly high fishery production. Purse seine Teri is one type of fishing gear used in PPP Larangan whose catch is fairly productive. The purpose of this research is to analyze the technical and financial aspects of capture fisheries business with purse seine Teri. The material used in this research is 8 units of purse seine Teri ship with lights. The method used is observation and interviews. Technical analysis includes the type of vessel, specifications fishing gear, and methods operation of fishing gear. Based on the technical analysis, the comparison of the dimensions of the vessel and the fishing gear is in accordance with the technical guidelines, namely the length of the fishing gear is at least 15 times the length of the vessel. The length of the bottom ris rope is an average of 13% of the top ris rope and accordance with the standart technical guidelines, which is a minimum of 10%. The average length of the corrugated rope is 1,3 from the length of the bottom ris rope, which is in accordance with the technical guidelines, which is between 1,1 - 1,75. The mesh size of the 0,5 inch is still safe because it is under the provisions of the technical guide, which is 0,6 inch